Isolation of entomopathogenic nematodes in an apple orchard in Southern Brazil and its virulence to Anastrepha fraterculus (Diptera: Tephritidae) larvae, under laboratory conditions - Foelkel,E. (2017)
Abstract Entomopathogenic nematodes (EPNs) are a promising alternative to integrated control in many fruit pests. Few studies were made on the relationship of Anastrepha fraterculus natural population with native EPNs population and other biotic and abiotic factors. The aim of this work was to verify the occurrence of endemic nematodes in an apple orchard, concerning environmental conditions and technical procedure, and access isolates virulence to A. fraterculus larvae. The experiment was conducted during a year taking monthly soil samples from an apple orchard, with and without fallen fruits just above the soil. Samples were baited with Tenebrium molitor and A. fraterculus larvae in laboratory. Canopy and fallen fruits were sampled to access the pest infestation. Seventy three EPN isolates were captured, in 23.2% soil samples, more with T. molitor than with A. fraterculus baits. From the 20 isolates tested against A. fraterculus, only five were pathogenic, and they were identified as Oscheius sp. The nematodes were captured during all seasons in a similar frequency. Soil and weather conditions, presence of fruit over the orchard soil, and A. fraterculus pupae in the fruits had no significant influence on the capture. As a conclusion, nematodes of the genera Oscheius are found in an apple orchard of Porto Amazonas constantly along the year, independently of fluctuations in A. fraterculus population, climate conditions and presence of fruit over the soil. Some of the isolates are pathogenic to A. fraterculus.